2009
DOI: 10.1080/03602550903147270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixing Conditions on the Tensile Properties of Ethylene Vinyl Acetate/Waste Tire Dust (EVA/WTD) Blend

Abstract: Blends of Ethylene Vinyl Acetate/Waste Tire Dust (EVA/WTD) were prepared by using a Haake Rheomix at 100/0, 90/10, 80/20, 70/30, and 60/40 blend ratios. The effect of mixing temperature, blend ratio and blending time on the tensile properties of EVA/ WTD blends were investigated. The mixing time was varied from 5 to 30 minutes, while the mixing temperature was varied from 120 to 160 C. The tensile properties of the blends found to show a gradual decrease with the addition of WTD. EVA/WTD blends prepared at 140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…In general, the properties of GTR/RTR containing polymer decrease with increasing GTR/RTR content [34,48,49] caused by poor interfacial adhesion between the blend components. These blends are simply a physical mixture of two incompatible polymers, in which the continuous matrix phase is largely responsible for the mechanical properties.…”
Section: Compatibilizationmentioning
confidence: 98%
“…In general, the properties of GTR/RTR containing polymer decrease with increasing GTR/RTR content [34,48,49] caused by poor interfacial adhesion between the blend components. These blends are simply a physical mixture of two incompatible polymers, in which the continuous matrix phase is largely responsible for the mechanical properties.…”
Section: Compatibilizationmentioning
confidence: 98%
“…Another work utilizing EVA and GTR also reported the tensile properties of the blends decreased with increasing GTR loading (TS and Eb drop by ≈60% while TM drop by ≈25% at 40 wt% GTR) as per volume rate of additivity where the higher strength EVA molecules are gradually replaced by the lower strength of GTR phase (Sakinah et al, 2009). Li et al (2003a) incorporated cryogenically ground GTR into HDPE matrix and found the Eb and impact strength deteriorated by more than 90% and 80% respectively.…”
Section: Gtr/rtr Loadingmentioning
confidence: 99%
“…In general, the properties of GTR/RTR containing polymer decrease with increasing GTR/RTR content , Sakinah et al, 2009, Sonnier et al, 2007 caused by poor interfacial adhesion between the blend components.…”
Section: Compatibilizationmentioning
confidence: 99%
“…that the addition of BADGE to the EVA/WTD blend caused a sharp decrease in mixing torque. This is due to the plasticizing effect of the compatibilizer, which is believed to act as an internal lubricant to the blend . The higher the ratio of BADGE, the higher the lubricating effect, hence lowered viscosity, leading to the lower initial mixing torque of the blend.…”
Section: Resultsmentioning
confidence: 99%
“…EVA is a copolymer made from two monomers, ethylene and vinyl acetate (VA), whose properties depend on the content of VA, such that EVA with <2 0 wt% VA content can be used as thermoplastics , for different applications, such as footwear components, flexible hose, automobile bumpers, toys and athletic goods, molded automotive parts, flexible packaging, and films. Several studies have been carried out by blending waste tire dust (WTD) with PP , rHDPE , NR , and EVA , which in turn improved the mechanical properties of the WTD. However, Ramli et al reported reduced mechanical properties for EVA/WTD composite due to poor interfacial bonding and agglomeration upon filler loading.…”
Section: Introductionmentioning
confidence: 99%